Chrysanthemum - Henkes, Kevin (New York : Mulberry Books, 1996)
Chrysanthemum loves her name, until she starts going to school and the other children make fun of it.
72340
Keywords: Names, Personal -- Juvenile fiction; Schools -- Juvenile fiction